Black African asylum seekers' experiences of health care access in an eastern German state - Penelope Scott (International Journal of Migration, Health and Social Care, 2014)
[Purpose:] The purpose of this paper is to examine how access to health care for (rejected) asylum seekers in an eastern German state is structured and experienced and to consider the implications for their human rights. [Design/methodology/approach:] The paper is based on 12 in-depth interviews with rejected black African asylum seekers and also draws on ethnographic research undertaken at a grassroots refugee organisation and asylum homes. The analysis of the interview data are framed by theorisations of “everyday practices” as “tactics” of resistance to an imposed order. [Findings:] Accomplishing health care access involved a range of structural barriers and humiliating interactions with administrative and health care staff, which had adverse consequences for their health status and were injurious to their human rights and dignity. The study participants used a range of oppositional and discursive tactics in an effort to secure certain (health) outcomes, mediate social relations and resist their domination as asylum seekers. [Research limitations/implications:] Further research should focus on the cumulative micro-level effects of asylum policies on health care access and how they create health inequities and violate asylum seekers' rights and dignity. [Practical implications:] Policy priorities should include the provision of human rights education as well as training and support for administrative and health staff. [Originality/value:] There is limited qualitative research on the health care experiences of asylum seekers in Germany. This paper makes policy recommendations and identifies areas for further research and human rights advocacy.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; Germany; asylum seekers; black Africans; discrimination; health inequities; health care; human rights; qualitative research